Activation of M3 cholinoceptors attenuates vascular injury after ischaemia/reperfusion by inhibiting the Ca2+/calmodulin‐dependent protein kinase II pathway. (16th June 2015) - Lu, Xing‐Zhu; Bi, Xue‐Yuan; He, Xi; Zhao, Ming; Xu, Man; Yu, Xiao‐Jiang; Zhao, Zheng‐Hang; Zang, Wei‐Jin
Abstract : Background and Purpose: The activation of M3 cholinoceptors (M3 receptors) by choline reduces cardiovascular risk, but it is unclear whether these receptors can regulate ischaemia/reperfusion (I/R)‐induced vascular injury. Thus, the primary goal of the present study was to explore the effects of choline on the function of mesenteric arteries following I/R, with a major focus on Ca 2+ /calmodulin‐dependent protein kinase II (CaMKII) regulation. Experimental Approach: Rats were given choline (10 mg·kg −1, i.v.) and then the superior mesenteric artery was occluded for 60 min (ischaemia), followed by 90 min of reperfusion. The M3 receptor antagonist, 4‐diphenylacetoxy‐N‐methylpiperidine methiodide (4‐DAMP), was injected (0.12 μg·kg −1, i.v.) 5 min prior to choline treatment. Vascular function was examined in rings of mesenteric arteries isolated after the reperfusion procedure. Vascular superoxide anion production, CaMKII and the levels of Ca 2+ ‐cycling proteins were also assessed. Key Results: Choline treatment attenuated I/R‐induced vascular dysfunction, blocked elevations in the levels of reactive oxygen species (ROS) and decreased the up‐regulated expression of oxidised CaMKII and phosphorylated CaMKII. In addition, choline reversed the abnormal expression of Ca 2+ ‐cycling proteins, including Na + /Ca 2+ exchanger, inositol 1, 4, 5‐trisphosphate receptor, sarcoplasmic reticulum Ca 2+ ‐ATPase and phospholamban. All of these cholinergic effects of choline were abolished by 4‐DAMP. Conclusions and Implications: Our data suggest that inhibition of the ROS‐mediated CaMKII pathway and modulation of Ca 2+ ‐cycling proteins may be novel mechanisms underlying choline‐induced vascular protection. These results represent a significant addition to the understanding of the pharmacological roles of M3 receptors in the vasculature, providing a new therapeutic strategy for I/R‐induced vascular injury. Linked Articles: This article is part of a themed section on Chinese Innovation in Cardiovascular Drug Discovery. To view the other articles in this section visithttp://dx.doi.org/10.1111/bph.2015.172.issue-23